Influence of selected food in the profilactice and treatment of osteoporosis - Gorzyński, Rafał; Kurek, Justyna; Gadomska, Anna; Molczyk-Sieńczak, Justyna; Garstka, Michał; Dominik, Hanna; Czudy, Zuzanna; Pawęska, Wojciech; Polatowska, Marika; Radwański, Jan (Journal of Education, Health and Sport, 2023)
Introduction: The proper diet plays an extremely important role in the development of the skeletal system from an early age This is one of the few modifiable factors that we can influence by choosing the right food. In the case of osteoporosis, nutrition is not only important during the period of growth, but also for the rest of life, which allows to reduce pathological changes in bones and counteract the effects of reduced bone mineral density such as fractures or death. Purpose of the work: The aim of the study was to answer the question of which nutrients have a significant impact on bone tissue metabolism and minimize the risk of osteoporosis and its consequences, as well as what substances contained in food may be used in the future by medicine for preventive purposes. Summary: Without a doubt, the provision of adequate recommended doses of nutrients with food is crucial for the prevention and treatment of osteoporosis and its consequences, but it should be remembered that the recommended doses are averaged. As studies show, the absorption of the described substances can vary depending on the food contained in the diet, as well as the age of a person, so the recommended doses of patients should be obtained individually, taking into account dietary preferences and laboratory results. In addition, compounds such as isoflavones, while promising in the prevention of this condition, should not be routinely used as a replacement for estrogen hormone therapy, due to the still small amount of research and their ambiguous results. It is worth remembering that often the diet turns out to be an insufficient preventive measure and should be combined with pharmacotherapy. Materials and methods: Literature review in the database PubMed, Google Scholar, Springer Link, MDPI, using the keywords: Osteoporosis, diet, calcium, phosphorus, vitamin D, Vitamin K, magnesium, isoflavone.